Pengaruh Sikap dan Kebiasaan terhadap Hasil Belajar Matematika - Nurhayati Nurhayati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2011)
The general objective of this research is to discover and analyze empirically the effect of attitudes toward mathematics learning outcomes, learning habits influence on mathematics learning outcomes, influence attitudes and study habits together towards mathematics learning outcomes. The population covered in this study were junior high school grade students in District VIII Kramat Jati, East Jakarta. The research sample was obtained through random sampling method, the researchers mixed quota subjects in the population so that all subjects are considered equal. The research design used by the correlation technique with three variables consisting of two independent variables, namely student attitudes and study habits as well as a dependent variable, is mathematics learning outcomes. Data collected by questionnaire technique (variable attitudes and habits students learn) and test techniques (variable learning outcomes). Collected data are then analyzed using correlation and simple regression techniques and correlation and multiple regression. Before the data were analyzed, first performed descriptive statistical analysis and test data requirements (test of normality, linearity test). The results showed that: (1) there is significant influence between students' attitudes and habits towards learning mathematics learning outcomes, with a correlation coefficient of 0.465 and coefficient of determination of 0.216 or 21.6% of student attitude and study habits jointly affect the results of learning mathematics. The resulting regression equation Y = 7932 + 0, 377 X1 + 0, 257 X2. This could mean that the better the attitude of the students then the better the better the result of learning and study habits, the higher the results of studying mathematics.